2003
DOI: 10.1194/jlr.m200225-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosylphosphorylcholine is upregulated in the stratum corneum of patients with atopic dermatitis

Abstract: To clarify the functional relevance of sphingomyelin (SM) deacylase to the ceramide deficiency seen in atopic dermatitis (AD), we developed a new highly sensitive method and measured the metabolic intermediate sphingosylphosphorylcholine (SPC) that accumulates in the stratum corneum. SPC in intercellular lipids extracted from stratum corneum was reacted with [ 14 C]acetic anhydride to yield [ 14 C-C 2 ]SM, which was then analyzed by TLC. In both the lesional and non-lesional stratum corneum obtained from patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 23 publications
2
53
0
Order By: Relevance
“…The identification of pruritogen is one of ways to clarify the mechanism of pruritus and clues for therapeutics. Gsp is upregulated in the lesional skin of patients from atopic dermatitis (Okamoto et al, 2003). We speculate that abnormal skin barrier itself contributed to the symptoms of atopic dermatitis.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The identification of pruritogen is one of ways to clarify the mechanism of pruritus and clues for therapeutics. Gsp is upregulated in the lesional skin of patients from atopic dermatitis (Okamoto et al, 2003). We speculate that abnormal skin barrier itself contributed to the symptoms of atopic dermatitis.…”
Section: Discussionmentioning
confidence: 97%
“…The activity of sphingomyelin deacylase, in fact, is markedly higher in patients with atopic dermatitis than in healthy individuals. Glucosylsphingosine (Gsp) is increased in skin of patients with atopic dermatitis (Okamoto et al, 2003). Gsp, a metabolic precursor of glucocerebroside synthesis, also accumulates in the cerebral and cerebellar cortex in patients both with type 2 and 3 Gaucher disease (Nilsson and Svennerholm, 1982;Orvisky et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…We have shown that the putative lipid second messenger sphingosylphosphorylcholine (SPC) (12,13) binds specifically to both apo-and Ca 2ϩ -saturated CaM, and inhibits the action of the protein on the target enzymes phosphodiesterase and calcineurin (14). Data on SPC metabolism is still scarce, but its presence has been demonstrated under several physiologic and pathologic conditions (15)(16)(17)(18). Our findings suggest a novel endogenous regulation for CaM and also proposes that CaM might be an intracellular receptor for the sphingolipid.…”
Section: Calmodulin (Cam)mentioning
confidence: 97%
“…The interactions it can actually modify in vivo are probably selected by their cellular localization. Currently our knowledge of SPC metabolism is scarce (15)(16)(17)(18), so to accurately address this question, further study into the mechanism and location of in vivo SPC production is necessary. Nevertheless, experiments carried out with micelles containing other lipids besides SPC confirmed that SPC can displace CaM from its targets even when incorporated into a mixed lipid environment.…”
Section: Spc Exerts Its Effects In Mixed Micelles More Relevant To Imentioning
confidence: 99%
“…In patients with atopic dermatitis, the amount of ceramide in the stratum corneum decreases, and there is an inverse correlation between ceramide and sphingosylphosphorylcholine (SPc) levels in the lesional stratum corneum. 29) In the epidermis of patients with atopic dermatitis, the activity of sphingomyelin glucosylceramide deacylase is increased, and sphingomyelin and glucocerebroside are converted to SPc and glucosylsphingosine, respectively, by this enzyme, which results in the decrease in ceramide, leading to skin dryness and the disruption of the skin barrier. 30) SPc downregulates filaggrin gene transcription, which also leads to skin dryness and the disruption of the skin barrier.…”
Section: Lipid Mediatorsmentioning
confidence: 99%